Determinación de los niveles de contaminación a la atmosfera por emisiones de co2 en fuentes móviles de la ciudad de Zamora, provincia de Zamora Chinchipe - Sarango Peláez, Katty Yesela (2016)
Air pollution is a topic is of global concern that concerns around the world that over the years it is increasing, in the city of Zamora the problem cannot overlook, for this reason there has been realized the present work of qualification, the same one that is structured by the following parts: a) literature review b) Methodology, c) Results, d) Conclusions and recommendations. The literature review is composed of current regulations, scientific facts, other studies and basic concepts focused on reason for better understanding the same The methodology used in the research was the following: identification of the mobile sources through secondary information provided by the National Agency Transit, taxi companies and urban bus from the city of Zamora; a count was done in situ the mobile sources; surveys were carried out to the owners of vehicles; to different petrol stations of the city; was a route of 5 km with mobile sources selected previously; was calculated fuel consumption; conducted a calculation of emission of CO2. Regarding the results obtained using different methodologies, in the city of Zamora are emitted to the environment approximately 19 tons of CO2 per year. In conclusion, a total of CO2 emitted to the atmosphere by mobile sources was obtained is 19,095.24 tons annually. Recommending of Municipal GAD establish entities to the monitoring of gases, in particular CO2, with the purpose of establishing the critical points of emissions in the city.